2004
DOI: 10.1111/j.1460-2695.2004.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser shock peening on fatigue crack growth behaviour of aluminium alloy

Abstract: A B S T R A C TThe effect of laser shock peening (LPS) in the fatigue crack growth behaviour of a 2024-T3 aluminium alloy with various notch geometries was investigated. LPS was performed under a 'confined ablation mode' using an Nd: glass laser at a laser power density of 5 GW cm −2 . A black paint coating layer and water layer was used as a sacrificial and plasma confinement layer, respectively. The shock wave propagates into the material, causing the surface layer to deform plastically, and thereby, develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…In their report, the residual stress profiles of the treated samples after multiple LSP impacts with the impact time as functions of the distance from the top surface are shown in Figure 41. The substrates are approximately in the zero-stress state, indicating that the effect of initial stress on the shock waves may be ignored (Tan et al, 2004). It can be noted from Figure 41 that the significant compressive residual stresses mainly exist in near-surface regions for all cases and the top surfaces have the maximum values of compressive residual stresses (Lu et al, 2010).…”
Section: Laser Shock Peening Of Aluminium Alloysmentioning
confidence: 94%
“…In their report, the residual stress profiles of the treated samples after multiple LSP impacts with the impact time as functions of the distance from the top surface are shown in Figure 41. The substrates are approximately in the zero-stress state, indicating that the effect of initial stress on the shock waves may be ignored (Tan et al, 2004). It can be noted from Figure 41 that the significant compressive residual stresses mainly exist in near-surface regions for all cases and the top surfaces have the maximum values of compressive residual stresses (Lu et al, 2010).…”
Section: Laser Shock Peening Of Aluminium Alloysmentioning
confidence: 94%
“…LSP-induced residual stresses can be used to improve the damage tolerance behaviour of lightweight metallic structures. Several researches investigated the effects of LSP on the initiation and propagation of fatigue cracks in aluminium alloy specimens with various notch geometries [1,[5][6][7][8][9]. The results clearly demonstrated that LSP can be used as an effective surface treatment technique for reducing or suppressing fatigue crack growth in aluminium alloys.…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, and in a parallel way, the technique has been successfully studied from a practical point of view and applied to a number of relevant material-geometry configurations involving structural materials in the aerospace, automotive, nuclear, and biomedical sectors (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75), its beneficial effects on static, fatigue and corrosion properties having been widely demonstrated .…”
Section: Introduction: the Laser Shock Processing Techniquementioning
confidence: 99%